2017
DOI: 10.1002/ange.201708746
|View full text |Cite
|
Sign up to set email alerts
|

High Sulfur Content Material with Stable Cycling in Lithium‐Sulfur Batteries

Abstract: We demonstrate a novel crosslinked disulfide system as a cathode material for Li‐S cells that is designed with the two criteria of having only a single point of S−S scission and maximizing the ratio of S−S to the electrochemically inactive framework. The material therefore maximizes theoretical capacity while inhibiting the formation of polysulfide intermediates that lead to parasitic shuttle. The material we report contains a 1:1 ratio of S:C with a theoretical capacity of 609 mAh g−1. The cell gains capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Lithium–sulfur batteries (LSBs) are considered promising candidates for next-generation energy storage equipment, on account of their high theoretical specific capacity (1675 mAh g –1 ) and energy density (2600 Wh kg –1 ). Simultaneously, elemental sulfur is low-cost, environmentally friendly, and abundant in nature . Nevertheless, the applications of LSBs are limited by three main issues: (1) poor conductivity of the elemental sulfur and the discharge products (Li 2 S and Li 2 S 2 ), (2) large volumetric expansion (80%) from sulfur to Li 2 S, and (3) the “shuttle effect” produced by soluble LiPSs (Li 2 S n , 4 ≤ n ≤ 8), which lead to a loss of the sulfur, poor cycle stability of the LSBs, and serious security problems. For solving the above-mentioned problems, the combination of sulfur and carbonaceous materials has been regarded as a common way because of the good conductivity of carbon materials. Nazar and co-workers first proposed the highly ordered mesoporous carbon (CMK-3) as the host materials of sulfur, and the resultant LSBs showed good electrochemistry performances .…”
Section: Introductionmentioning
confidence: 99%
“…Lithium–sulfur batteries (LSBs) are considered promising candidates for next-generation energy storage equipment, on account of their high theoretical specific capacity (1675 mAh g –1 ) and energy density (2600 Wh kg –1 ). Simultaneously, elemental sulfur is low-cost, environmentally friendly, and abundant in nature . Nevertheless, the applications of LSBs are limited by three main issues: (1) poor conductivity of the elemental sulfur and the discharge products (Li 2 S and Li 2 S 2 ), (2) large volumetric expansion (80%) from sulfur to Li 2 S, and (3) the “shuttle effect” produced by soluble LiPSs (Li 2 S n , 4 ≤ n ≤ 8), which lead to a loss of the sulfur, poor cycle stability of the LSBs, and serious security problems. For solving the above-mentioned problems, the combination of sulfur and carbonaceous materials has been regarded as a common way because of the good conductivity of carbon materials. Nazar and co-workers first proposed the highly ordered mesoporous carbon (CMK-3) as the host materials of sulfur, and the resultant LSBs showed good electrochemistry performances .…”
Section: Introductionmentioning
confidence: 99%
“…However, the key issues for Li–S batteries are the intrinsic insulating property of elemental sulfur and the shuttling effect of lithium polysulfide intermediate products (Li 2 S x , 4 ≤ x ≤ 8), which impede their development toward practical applications . To overcome these obstacles, enormous efforts have been conducted from the perspectives of (i) confining the polysulfides generated during battery operation in conductive host materials and (ii) avoiding the formation of such polysulfides via developing novel active materials that contain short chains of sulfur atoms, by which the Li–S batteries have seen substantial progress to date. , Recently, organosulfur electrodes consisting of S atoms/chains grafted in organic or polymeric matrices have been increasingly studied for addressing the polysulfide shuttling issue. Previous work by Zhang et al suggested that strong chemical interaction between sulfur and carbon favors inhibiting the shuttling effect . Remaining issues for such organosulfur materials are the limited intrinsic conductivity and relatively poor sulfur binding capability of their supporting skeletons, which lower the redox kinetics and sulfur utilization ratio.…”
mentioning
confidence: 99%
“…Poly­(disulfide)­s have gained much interest in recent years due to the dynamic nature of −S–S– bonds located in the main chain of polymers, which can be reversibly broken and reformed on demand . This striking behavior of the disulfide bond has been exploited in many areas ranging from material science to bio-related applications. Historically, oxidative polymerization is the simplest method to produce poly­(disulfide)­s. This strategy is based on the ability of thiol compounds to be oxidized by using air or an oxidizing agent to form a disulfide.…”
Section: Introductionmentioning
confidence: 99%